Reconstructing the Legal Framework of AI Use in Indonesia's 2024 Presidential Campaign: A Progressive and Responsive Law Perspective - Tasya, Izzuma; Susmayanti, Riana; Al-Uyun, Dhia (International Journal of Business, Law, and Education, 2025)
The rise of Artificial Intelligence (AI) in Indonesia's 2024 presidential campaign reveals a significant legal gap in Law No. 7 of 2017 on Elections. Using a normative juridical approach, this study examines the 1945 Constitution, Election Law, and Constitutional Court Decision No. 166/PUU-XXI/2023. Findings show that while the Court prohibits "excessive” AI manipulation under the notion of citra diri (self-image), no binding technical rules exist to govern its use. The study employs the theories of Radbruch's Legal Purpose, Satjipto Rahardjo’s Progressive Law, and Nonet–Selznick's Responsive Law to analyse justice, certainty, and social benefit in regulating AI campaigns. It concludes that AI-driven campaigning through avatars, deepfakes, and microtargeting poses constitutional risks unless addressed by adaptive, participatory, and justice-oriented regulation. Thus, responsive and progressive legal reform is crucial to preserving electoral integrity and democratic legitimacy in the digital era.